Hydrogen anion conductor and preparation method and application thereof

By incorporating alkaline earth metal compounds into rare earth metal binary hydrides to form new hydrogen negative ion conductors, the problem of poor conductivity of existing conductors at medium and low temperatures and room temperatures is solved, excellent performance at lower temperatures is achieved, and the application scope of electrochemistry is broadened.

CN119724677APending Publication Date: 2025-03-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311272029.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing hydrogen negative ion conductors have poor ionic conductors at medium and low temperatures and room temperatures, which has not yet been widely promoted in the field of electrochemistry.

Method used

The alkaline earth metal compound is incorporated into rare earth metal binary hydride to form a new hydrogen negative ion conductor, and its performance and application are studied through synthesis methods.

Benefits of technology

It exhibits excellent performance at lower temperatures, broadens the research system and application range of solid electrolyte materials, and has excellent ionic conductivity performance at high temperature and room temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724677A_ABST
    Figure CN119724677A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrogen anion conductor and a preparation method and application thereof. The hydrogen anion conductor comprises a rare earth metal hydride and a main group metal compound, the main group metal compound is selected from alkali metal compounds and / or alkaline earth metal compounds; the molar ratio of main group metal elements in the main group metal compound to rare earth metal elements in the rare earth metal hydride is (2: 1)-(1: 7). According to the invention, a material containing an alkali (soil) metal compound and a rare earth metal hydride is used as a hydrogen anion conductor. The conductor material comprises two components, namely an alkali (earth) metal compound and a rare earth metal hydride; the molar ratio of the alkali metal to the rare earth metal element is 2: 1-1: 7. The material shows excellent ionic conductivity at room temperature and medium-high temperature, and is expected to be applied to hydrogen anion batteries, fuel cells, electroreduction reaction devices and the like. According to the invention, the research system of metal hydride and solid electrolyte materials and the application range of the research system are greatly widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a hydrogen anion conductor and a preparation method and application thereof, belonging to the field of material technology. Background Art

[0002] When hydrogen forms a compound, it can easily lose an electron to become a proton, or gain an electron to become a hydrogen ion. - The radius of the ion is larger than that of F - , O 2- It is similar to hydrogen ion, but it only contains one valence charge, so the charge density is small and it is easier to polarize. This is very different from proton conduction in materials. Protons have a high charge density and tend to be strongly bonded to O in oxides, with a high activation energy. In addition, the standard redox potential of hydrogen ions is -2.3V, close to that of magnesium ions (-2.4V), but its atomic mass is only 1 / 24 of that of magnesium, which makes it a promising ion conductor material for a new generation of high energy density and high potential batteries. - The rapid conduction of ions is expected to realize a series of technological innovations, including new H - All-solid-state batteries, gas sensors, separation membranes, membrane reactors, and various catalytic reactions, etc.

[0003] Some hydrogen anion conductors have been reported, mainly in two categories: one is based on alkaline earth metals, including binary hydrides, oxyhydrides, and halogenides; the other is based on rare earth metals, mainly oxyhydrides. There are still few research systems for hydrogen anion conductors, and most systems have poor ionic conductivity at low and medium temperatures and room temperature, resulting in a lack of application in the field of electrochemistry.

[0004] Rare earth metal binary hydrides are usually face-centered cubic structures, with rare earth metals occupying face-center and vertex positions, and forming multiple tetrahedral and octahedral gaps. Hydrogen occupies tetrahedral gaps first, and then octahedral gaps. When the amount of hydrogen is insufficient or the synthesis conditions are different, tetrahedral and octahedral vacancies may be formed, and tetrahedral H and octahedral H are each other's nearest neighbors. These characteristics provide an environment that is conducive to hydrogen migration. However, there are currently no reports on the direct doping of alkali (earth) metal compounds into rare earth metal binary hydrides as hydrogen anion conductors, and this field is still blank. Summary of the invention

[0005] The invention discloses that alkaline (earth) metal compounds are doped with rare earth metal binary hydrides as hydrogen anion conductors, which exhibit excellent performance at relatively low temperatures. This invention will greatly broaden the research system and application scope of solid electrolyte materials.

[0006] The present invention provides a new synthesis method of hydrogen anion conductor and its application research. Specifically, the hydrogen anion conductor material is synthesized using rare earth metal hydride and alkaline (earth) metal compound as raw materials, and the performance and application of the hydrogen anion conductor are studied.

[0007] The present invention provides a hydrogen anion conductor, which comprises an alkali (earth) metal compound and a rare earth metal binary hydride, wherein the rare earth metal binary hydride has a chemical formula of REH x ;

[0008] Here, RE represents a rare earth metal, and x ranges from 1 to 10.

[0009] According to one aspect of the present application, a hydrogen anion conductor is provided, wherein the hydrogen anion conductor comprises a rare earth metal hydride and a main group metal compound;

[0010] The main group metal compound is selected from alkali metal compounds and / or alkaline earth metal compounds;

[0011] The molar ratio of the main group metal element in the main group metal compound to the rare earth metal element in the rare earth metal hydride is 2:1 to 1:7.

[0012] Optionally, the alkali metal element in the alkali metal compound is selected from at least one of lithium, sodium, potassium, rubidium and cesium.

[0013] Optionally, the alkaline earth metal element in the alkaline earth metal compound is selected from at least one of magnesium, calcium, strontium and barium.

[0014] Optionally, the rare earth metal element is selected from at least one of scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium.

[0015] Optionally, the main group metal compound is selected from at least one of main group metal elements, main group metal hydrides, main group metal nitrides, main group metal halides, main group metal oxides, main group metal sulfides, main group metal carbonyl compounds, and main group metal carbides.

[0016] Optionally, the alkaline (earth) metal compound is selected from at least one of an alkaline (earth) metal element, an alkaline (earth) metal alloy, an alkaline (earth) metal hydride, an alkaline (earth) metal nitride, an alkaline (earth) metal halide, an alkaline (earth) metal oxide, an alkaline (earth) metal sulfide, an alkaline (earth) metal carbonyl, and an alkaline (earth) metal carbide.

[0017] According to another aspect of the present application, a method for preparing the above-mentioned hydrogen anion conductor is provided, the preparation method comprising:

[0018] The negative hydrogen ion conductor is obtained by mixing a mixture containing a rare earth metal hydride and a main group metal compound; or a mixture containing a rare earth metal hydride and a main group metal element is reacted to obtain the negative hydrogen ion conductor.

[0019] Optionally, the mixing or reaction conditions are selected from at least one of ball milling, calcination, and stirring.

[0020] Optionally, the ball milling conditions are: the ball milling pressure is 0.1-1 MPa, and the ball milling temperature is 10-100°C.

[0021] Optionally, the ball milling pressure is selected from any value among 0.1 MPa, 0.2 MPa, 0.5 MPa, 0.7 MPa, 1.0 MPa or a range between any two of the above values.

[0022] Optionally, the ball milling temperature is selected from any value of 10°C, 20°C, 50°C, 70°C, 80°C, 100°C or a range between any two of the above values.

[0023] Optionally, the rotation speed of the ball mill is 50-600 rpm, and the ball-to-material ratio is (20-120):1.

[0024] Optionally, the rotation speed of the ball mill is selected from any value of 50rpm, 100rpm, 150rpm, 200rpm, 250rpm, 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 600rpm or a range between any two of the above values.

[0025] Optionally, the ball-to-material ratio is selected from any value among 20:1, 30:1, 50:1, 80:1, 100:1, 120:1 or a range between any two of the above values.

[0026] Optionally, the calcination pressure is 0.01 to 10 bar.

[0027] Optionally, the calcination pressure is selected from any value among 0.01 bar, 1 bar, 2 bar, 3 bar, 5 bar, 7 bar, 10 bar, or a range between any two of the above values.

[0028] Optionally, the calcination temperature is 200 to 500° C., and the calcination time is 1 to 30 hours.

[0029] Optionally, the calcination temperature is selected from any value of 200°C, 250°C, 300°C, 350°C, 400°C, 500°C or a range between any two of the above values.

[0030] Optionally, the calcination time is selected from any value of 1 h, 5 h, 10 h, 15 h, 20 h, 25 h, 30 h, or a range between any two of the above values.

[0031] Optionally, the heating rate during calcination is 1 to 10°C / min.

[0032] Optionally, the heating rate of the calcination is selected from any value of 1°C / min, 2°C / min, 3°C / min, 5°C / min, 7°C / min, 8°C / min, 10°C / min or a range between any two of the above values.

[0033] Optionally, the mixing or reacting further includes reacting in a reducing atmosphere or an inactive atmosphere.

[0034] Optionally, the reducing atmosphere is selected from at least one of hydrogen, carbon monoxide and methane.

[0035] Optionally, the inert atmosphere is selected from at least one of nitrogen, argon and helium.

[0036] Optionally, the stirring pressure is 0.1-10 MPa, and the stirring speed is 5000-30000 rpm.

[0037] Optionally, the stirring pressure is selected from any value of 0.1 MPa, 1 MPa, 2 MPa, 3 MPa, 5 MPa, 8 MPa, 10 MPa or a range between any two of the above values.

[0038] Optionally, the stirring rate is selected from any value of 5000 rpm, 10000 rpm, 15000 rpm, 20000 rpm, 25000 rpm, 30000 rpm or a range between any two of the above values.

[0039] Optionally, the stirring temperature is 10 to 100° C., and the stirring time is 1 to 40 hours.

[0040] Optionally, the stirring temperature is selected from any value of 10°C, 20°C, 30°C, 50°C, 70°C, 100°C or a range between any two of the above values.

[0041] Optionally, the stirring time is selected from any value of 1 h, 5 h, 10 h, 15 h, 20 h, 25 h, 30 h, 35 h, 40 h or a range between any two of the above.

[0042] Optionally, the preparation method of the negative hydrogen ion conductor comprises the following steps:

[0043] The rare earth metal hydride and the alkaline (earth) metal compound are reacted in a reducing atmosphere, a protective atmosphere or a vacuum environment by using any one of ball milling, calcination or stirring, the reaction product is ground into powder, and then the powder is extruded to form a hydrogen anion conductor.

[0044] Optionally, the method of processing the reaction product to form a hydrogen ion conductor is to grind the reaction product into powder and then extrude the powder into a hydrogen ion conductor.

[0045] Optionally, the method further comprises installing electrodes at both ends of the extruded hydrogen ion conductor.

[0046] According to another aspect of the present application, there is provided a use of the above-mentioned hydrogen anion conductor in a solid electrolyte.

[0047] According to another aspect of the present application, there is provided an application of the above-mentioned hydrogen anion conductor in constructing a new type of secondary battery, fuel cell, electrochemical reaction device, hydrogen separation membrane, sensor, and membrane reactor.

[0048] The present invention discloses a novel method for synthesizing a rare earth-based hydrogen anion conductor. - ) has strong reducing properties and high redox potential, is a highly reactive hydrogen source, and is a new type of energy carrier with great development potential. Hydrogen anion conductors have broad application prospects in research fields such as secondary batteries, fuel cells, electrochemical reactions, and hydrogen separation membranes, but there are few hydrogen anion conductor systems that have been discovered, and most of them require higher temperatures to have better ionic conductivity and mobility, resulting in their application in the field of electrochemistry is still blank. The present invention proposes to use a material containing an alkali (earth) metal compound composite rare earth metal hydride as a hydrogen anion conductor. The conductor material comprises two components, an alkali (earth) metal compound and a rare earth metal hydride; the alkali (earth) metal is selected from at least one of Li, Na, K, Rb, Cs, Mg, Ca, Sr, and Ba; the molar ratio of alkali metal to rare earth metal element is 2:1 to 1:7. It exhibits excellent ionic conductivity at room temperature and medium and high temperatures, and is expected to be used in hydrogen anion batteries, fuel cells, and electroreduction reaction devices. This invention will greatly broaden the research system and application scope of metal hydrides and solid electrolyte materials.

[0049] The beneficial effects of this application include:

[0050] This application is the first to use rare earth metal binary hydrides or mixtures of rare earth metal binary hydride main materials as hydrogen anion conductors, broadening the research scope of solid electrolyte systems. The hydrogen anion conductors developed by this method have excellent high temperature and even room temperature conductivity performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 The figure is a graph showing the change of ionic conductivity of NaH-4CeH3 synthesized in Example 1 of the present application as a function of temperature.

[0052] Figure 2 This is a graph showing the change in ionic conductivity of NaH-2CeH3 synthesized in Example 2 of the present application as a function of temperature.

[0053] Figure 3 This is a graph of impedance spectra at different temperatures of NdH3-10%LiH synthesized in Example 3 of the present application.

[0054] Figure 4 This is a curve chart showing the change of ionic conductivity of MgO-PrH3 synthesized in Example 4 of the present application with temperature. DETAILED DESCRIPTION

[0055] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0056] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0057] The instrument used in this application is: BioLogic VSP-300 electrochemical workstation.

[0058] The invention adopts a rare earth metal hydride and an alkaline (earth) metal compound to react in a reducing atmosphere, a protective atmosphere or a vacuum environment by using any one of ball milling, calcination or stirring, grinds the reaction product into powder, then extrude the powder into a hydrogen anion conductor, and studies the hydrogen anion conduction performance of the material.

[0059] Example 1: Preparation of NaH-4CeH3 and Study of Its Properties and Applications

[0060] (1) In a glove box, weigh 0.08 g of metallic Na and 2 g of CeH3, put them into a ball mill with a ball-to-material ratio of 40:1, fill the ball mill with 20 bar of H2, and ball mill for 10 h at a speed of 200 rpm. After running for 10 min, stop for 2 min and rotate in the opposite direction;

[0061] (2) 400 mg of the reaction product of step (1) was ground into a uniform powder using a mortar, and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0062] (3) The thin sheet obtained in step (2) was loaded into a stainless steel battery buckle. Nickel foam was used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle were tested using an electrochemical workstation. The test temperature was measured at 20°C, and one point was measured every 20°C. Each temperature point was kept constant for 2 hours before testing again. The curve of the ionic conductivity of NaH-4CeH3 changing with temperature is shown in Figure 1 As shown, from Figure 1 It can be seen that the conductivity of the material at 20℃ reaches 10 -4 S cm -1 The conductivity at 100℃ reaches 10 -3 S cm -1 It has good hydrogen ion conductivity.

[0063] Example 2: Preparation of NaH-2CeH3 and Study of Its Properties and Applications

[0064] (1) In a glove box, weigh 0.16 g of metallic Na and 2 g of CeH3, put them into a ball mill with a ball-to-material ratio of 40:1, fill the ball mill with 20 bar of H2, and ball mill for 10 h at a speed of 200 rpm. After running for 10 min, stop for 2 min and rotate in the opposite direction;

[0065] (2) 400 mg of the reaction product of step (1) was ground into a uniform powder using a mortar, and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0066] (3) The thin sheet obtained in step (2) was loaded into a stainless steel battery buckle. Nickel foam was used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle were tested using an electrochemical workstation. The test temperature was set at 20°C, and one point was measured every 20°C. Each temperature point was kept constant for 2 hours before testing again. The curve of the ionic conductivity of NaH-2CeH3 changing with temperature is shown in Figure 1. Figure 2 As shown, from Figure 2 It can be seen that the conductivity of the material at 20℃ reaches 10 -5 S cm -1 The conductivity at 100℃ reaches 10 -4 S cm -1 It has good hydrogen ion conductivity.

[0067] Example 3: Preparation of NdH3-10%LiH and study of its properties

[0068] (1) In a glove box, weigh 0.2 g of LiH and 2 g of NdH3, put them into a ball mill with a ball-to-material ratio of 40:1. The ball mill was filled with normal pressure Ar and ball milled for 10 h at a speed of 200 rpm. After running for 10 min, stop for 2 min and rotate in the opposite direction.

[0069] (2) 400 mg of the reaction product of step (1) was ground into a uniform powder using a mortar, and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0070] (3) The thin sheet obtained in step (2) was loaded into a stainless steel battery buckle. Nickel foam was used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum of the battery buckle was tested using an electrochemical workstation. The test temperature was programmed to rise from 20°C. Each temperature point was kept constant for 2 hours before testing again. The impedance spectrum of the ionic conductivity of NdH3-10%LiH as a function of temperature is shown in Figure 1. Figure 3 As shown, from Figure 3 It can be seen that the material exhibits considerable ionic conductivity at different temperatures.

[0071] Example 4: Preparation of MgO-3PrH3 and study of its properties

[0072] (1) In a glove box, weigh 0.2 g of MgO and 2 g of PrH3, put them into a mortar, and mix and grind for 1 hour;

[0073] (2) 400 mg of the reaction product of step (1) was taken and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0074] (3) The thin sheet obtained in step (2) was loaded into a stainless steel battery buckle. Nickel foam was used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle were tested using an electrochemical workstation. The test temperature was increased from 20°C, and each temperature point was kept constant for 2 hours before testing again. The curve of ionic conductivity of MgO-3PrH3 changing with temperature is shown in Figure 4 As shown, from Figure 4 It can be seen that the conductivity of the material at 20℃ reaches 10 -5 S cm-1 level, conductivity at 100℃ reaches 10 -3 S cm -1 The activation energy is large, and it exhibits good hydrogen anion conductivity.

[0075] Example 5: Preparation of K2S-3LaH3 and study of its properties

[0076] (1) 0.8 g of K2S and 2 g of LaH3 were weighed in a glove box, manually ground and mixed, and then calcined at 500°C for 30 h in a closed reactor under a calcination atmosphere of 50 bar hydrogen;

[0077] (2) 400 mg of the reaction product of step (1) was ground into a uniform powder using a mortar, and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0078] (3) The thin sheet obtained in step (2) is loaded into a stainless steel battery buckle, and nickel foam is used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle are tested using an electrochemical workstation. The test temperature is from 20°C, and one point is measured every 10°C. Each temperature point is kept constant for 2 hours before testing again.

[0079] Example 6: Preparation of 2DyH2-BaO and study of its properties

[0080] (1) In a glove box, weigh 0.85 g of BaO and 2 g of DyH2, put them into a ball mill with a ball-to-material ratio of 40:1, and place the mill in an atmospheric pressure Ar mill. Mill for 10 h at a speed of 200 rpm. After every 10 min of operation, stop for 2 min and rotate in the opposite direction.

[0081] (2) 400 mg of the reaction product of step (1) was ground into a uniform powder using a mortar, and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0082] (3) The thin sheet obtained in step (2) was loaded into a stainless steel battery buckle, and nickel foam was used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum of the battery buckle was tested using an electrochemical workstation. The test temperature was programmed to rise from 20°C, and each temperature point was kept constant for 2 hours before testing again.

[0083] Example 7: Preparation of Ca2N2-3LaH3 and study of its properties

[0084] (1) 0.69 g of Ca2N2 and 2 g of LaH3 were weighed in a glove box, manually ground and mixed, and then calcined at 500°C for 30 h in a closed reactor under a calcination atmosphere of 50 bar hydrogen;

[0085] (2) 400 mg of the reaction product of step (1) was ground into a uniform powder using a mortar, and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0086] (3) The thin sheet obtained in step (2) is loaded into a stainless steel battery buckle, and nickel foam is used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle are tested using an electrochemical workstation. The test temperature is from 20°C, and one point is measured every 10°C. Each temperature point is kept constant for 2 hours before testing again.

[0087] Example 8: Preparation of KBr-4LaH3 and Study of Its Properties

[0088] (1) 0.42 g of Ca2N2 and 2 g of LaH3 were weighed in a glove box, manually ground and mixed, and then calcined at 500°C for 30 h in a closed reactor with a calcination atmosphere of 50 bar hydrogen;

[0089] (2) 400 mg of the reaction product of step (1) was ground into a uniform powder using a mortar, and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0090] (3) The thin sheet obtained in step (2) is loaded into a stainless steel battery buckle, and nickel foam is used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle are tested using an electrochemical workstation. The test temperature is from 20°C, and one point is measured every 10°C. Each temperature point is kept constant for 2 hours before testing again.

[0091] Example 9: Preparation of Ca(CO)8-4EuH2 and Study of Its Properties

[0092] (1) 0.93 g of Ca(CO)8 and 2 g of EuH2 were weighed in a glove box, manually ground and mixed, and then calcined at 500 °C for 30 h in a closed reactor with a calcination atmosphere of 50 bar hydrogen;

[0093] (2) 400 mg of the reaction product of step (1) was ground into a uniform powder using a mortar, and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0094] (3) The thin sheet obtained in step (2) is loaded into a stainless steel battery buckle, and nickel foam is used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle are tested using an electrochemical workstation. The test temperature is from 20°C, and one point is measured every 10°C. Each temperature point is kept constant for 2 hours before testing again.

[0095] Example 10: Preparation of LiC6-3SmH3 and study of its properties

[0096] (1) 0.37 g of LiC6 and 2 g of SmH3 were weighed in a glove box, manually ground and mixed, and then calcined at 500 °C for 30 h in a closed reactor with a calcination atmosphere of 50 bar hydrogen;

[0097] (2) 400 mg of the reaction product of step (1) was ground into a uniform powder using a mortar, and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0098] (3) The thin sheet obtained in step (2) is loaded into a stainless steel battery buckle, and nickel foam is used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle are tested using an electrochemical workstation. The test temperature is from 20°C, and one point is measured every 10°C. Each temperature point is kept constant for 2 hours before testing again.

[0099] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A hydrogen ion conductor, characterized in that The hydrogen anion conductor comprises rare earth metal hydride and main group metal compound; The main group metal compound is selected from alkali metal compounds and / or alkaline earth metal compounds; The molar ratio of the main group metal element in the main group metal compound to the rare earth metal element in the rare earth metal hydride is 2:1 to 1:

7.

2. The hydrogen anion conductor according to claim 1, characterized in that The alkali metal element in the alkali metal compound is selected from at least one of lithium, sodium, potassium, rubidium and cesium; Preferably, the alkaline earth metal element in the alkaline earth metal compound is selected from at least one of magnesium, calcium, strontium and barium.

3. The hydrogen anion conductor according to claim 1, characterized in that The rare earth metal element is selected from at least one of scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium.

4. The hydrogen anion conductor according to claim 1, characterized in that The main group metal compound is selected from at least one of main group metal hydrides, main group metal nitrides, main group metal halides, main group metal oxides, main group metal sulfides, main group metal carbonyl compounds, and main group metal carbides.

5. The method for preparing a hydrogen anion conductor according to any one of claims 1 to 4, characterized in that: The preparation method comprises: The negative hydrogen ion conductor is obtained by mixing a mixture containing a rare earth metal hydride and a main group metal compound; or a mixture containing a rare earth metal hydride and a main group metal element is reacted to obtain the negative hydrogen ion conductor.

6. The preparation method according to claim 5, characterized in that: The mixing or reaction conditions are selected from at least one of ball milling, calcination, and stirring; Preferably, the ball milling conditions are: the ball milling pressure is 0.1-1 MPa, and the ball milling temperature is 10-100° C.; Preferably, the rotation speed of the ball mill is 50-600 rpm, and the ball-to-material ratio is (20-120):

1.

7. The preparation method according to claim 6, characterized in that: The calcination pressure is 0.01 to 10 bar; Preferably, the calcination temperature is 200-500°C and the calcination time is 1-30h; Preferably, the heating rate during calcination is 1-10°C / min.

8. The preparation method according to claim 6, characterized in that: The mixing or reacting also includes reacting in a reducing atmosphere or an inactive atmosphere; Preferably, the reducing atmosphere is selected from at least one of hydrogen, carbon monoxide and methane; Preferably, the inert atmosphere is selected from at least one of nitrogen, argon and helium; Preferably, the stirring pressure is 0.1-10 MPa, and the stirring rate is 5000-30000 rpm; Preferably, the stirring temperature is 10-100° C., and the stirring time is 1-40 hours.

9. Use of the hydrogen anion conductor according to any one of claims 1 to 4 in a solid electrolyte.

10. Use of the hydrogen anion conductor according to any one of claims 1 to 4 in constructing a new type of secondary battery, fuel cell, electrochemical reaction device, hydrogen separation membrane, sensor, membrane reactor.